PENGARUH PENGGUNAAN BLOOKET TERHADAP PENILAIAN SUMATIF PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X DI SMA NEGERI 1 KARAWANG - Shaf, Al Kautsar; Debibik Nabilatul Fauziah; Neng Ulya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early reading ability is a basic skill that must be mastered by first grade elementary school students as a foundation in developing literacy skills. However, there are still students who experience difficulties in recognizing letters, reading syllables, reading words, and understanding reading. This study aims to determine the effectiveness of using the reading aloud method assisted by Digital Digestive-Friendly Books Category B2 on the early reading ability of first grade students at SDN Babelan Kota 03. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research sample consisted of an experimental class given treatment using the reading aloud method assisted by Digital Digestive-Friendly Books Category B2 and a control class using conventional learning. Data collection was carried out using the Early Grade Reading Assessment (EGRA) instrument, while data analysis included normality tests, homogeneity tests, hypothesis tests using the Mann–Whitney U test, and gain analysis. The results showed that there was a significant difference in the early reading ability between students in the experimental class and the control class based on the results of the Mann–Whitney U test on post-test scores, with an Asymp. Sig. value. (2-tailed) of 0.001 (<0.05). These results indicate that H₀ is rejected and H₁ is accepted, so that the use of the reading aloud method assisted by Digital Digestive-Friendly Books Category B2 is proven to be effective in improving the initial reading ability of first-grade elementary school students. These findings are reinforced by the results of the analysis of the gain score (the difference between pre-test and post-test scores) which also show a difference in the increase in initial reading ability between the experimental class and the control class, with an Asymp. Sig. (2-tailed) value of 0.015 (<0.05). Thus, it can be concluded that the use of the reading aloud method assisted by Digital Digestive-Friendly Books Category B2 is effective in improving the initial reading ability of first-grade elementary school students at SDN Babelan Kota 03.